Electronic device conventional current version - Floyd, Thomas L. (Pearson Prentice Hall, 2008)
This popular, up-to-date devices book takes a strong systems approach that identifies the circuits and components within a system, and helps readers see how the circuit relates to the overall system function. Floyd is well known for straightforward, understandable explanations of complex concepts, as well as for non-technical, on-target treatment of mathematics. The extensive use of examples, Multisim simulations, and graphical illustrations makes even complex concepts understandable. From discrete components, to linear integrated circuits, to programmable analog devices, this books¿ coverage is well balanced between discrete and integrated circuits. Also includes focus on power amplifiers; BJT and FET amplifiers; advanced integrated circuits-instrumentation and isolation amplifiers; OTAs; log/antilog amplifiers; and converters. Thorough coverage of optical topics-high intensity LEDs and fiber optics. Devices sections on differential amplifiers and the IGBT (insulated gate bipolar transistor) are now included. For electronics technicians.